2020
DOI: 10.21829/myb.2020.2631943
|View full text |Cite
|
Sign up to set email alerts
|

Registro y ecología de Zadiprion howdeni (Hymenoptera: Diprionidae) en Ixltán de Juárez, Oaxaca

Abstract: En los bosques de Ixtlán de Juárez se detectó un brote inusual de mosca sierra (Hymenoptera: Diprionidae), por lo que este trabajo tiene como objetivo identificar taxónomicamente a la especie afectante y estimar su densidad y ciclo de vida. La identificación se basó en la observación de especímenes adultos de ambos sexos, siguiendo las claves taxonómicas desarrolladas por David R. Smith y colaboradores. La densidad de capullos se evaluó en 10 sitios, dentro de los que se seleccionó al azar un árbol, a partir d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 9 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Severe infestations by a sawfly of the genus Zadiprion were reported in the Sierra Norte of Oaxaca from 2015 to 2021. This species was initially identified as Z. falsus (Suárez-Mota et al, 2018) and subsequently as Z. howdeni (Aguirre-Hidalgo et al, 2020). The present study, after a detailed review of field-collected and laboratory-reared specimens, showed that the external morphological and ovipositor characteristics of the female do not correspond to Z. falsus, Z. howdeni or any of the other species so far recognized.…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…Severe infestations by a sawfly of the genus Zadiprion were reported in the Sierra Norte of Oaxaca from 2015 to 2021. This species was initially identified as Z. falsus (Suárez-Mota et al, 2018) and subsequently as Z. howdeni (Aguirre-Hidalgo et al, 2020). The present study, after a detailed review of field-collected and laboratory-reared specimens, showed that the external morphological and ovipositor characteristics of the female do not correspond to Z. falsus, Z. howdeni or any of the other species so far recognized.…”
Section: Introductionmentioning
confidence: 48%
“…En la Sierra Norte de Oaxaca, de 2015 a 2021, se reportaron infestaciones severas por una mosca sierra del género Zadiprion. Inicialmente, la especie fue identificada como Z. falsus (Suárez-Mota et al, 2018) y posteriormente como Z. howdeni (Aguirre-Hidalgo et al, 2020). En el presente estudio, luego de una revisión detallada de especímenes recolectados en campo y de los criados en laboratorio, se encontró que las características morfológicas externas y del ovipositor de la hembra no corresponden a Z. falsus, Z. howdeni o a alguna de las otras especies hasta ahora reconocidas.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Recently, the community has faced infestations of defoliating insects and bark beetles. For their control and combat, guidelines should be followed for identification, determining the distribution, and defining phytosanitary treatments [57][58][59].…”
Section: Comparison Of Sub-stand Variables Of the Three Forest Manage...mentioning
confidence: 99%
“…In forestry, gregarious or solitary larval pine sawflies (Hymenoptera: Diprionidae) can cause problems of economic importance [8] and could be associated with outbreaks in their natural distribution sites, as well as recognized as invasive species [9][10][11].…”
Section: Introductionmentioning
confidence: 99%